Speech text of MoU handover ceremony memorandum of understanding between Universiti Teknologi MARA and Inner Mongolia University of Technology (IMUT) / Prof. Datuk Dr. Shahrin Sahib @ Sahibuddin - Sahib @ Sahibuddin, Shahrin (2024)
1. Alhamdulillah, thanks be to Allah S.W.T for His grace and blessings, permitting us to come together on this auspicious occasion. 2. Allow me to extend a warm welcome and Selamat Datang to everyone in attendance. It is a great pleasure and honour to be here with all of you to witness a significant milestone in our academic journey as we partake in the Handover Ceremony of the Memorandum of Understanding between Universiti Teknologi MARA (UiTM) and Inner Mongolia University of Technology (IMUT).